‘They didn’t look at me with good eyes' – experiences of the socioeconomic impact of tuberculosis and support needs among adults in a semi-rural area in Mozambique: A Qualitative Study - Pedroso Nhassengo; Clara Yoshino; Américo Zandamela; Verónica De Carmo; Bo Burström; Knut Lönnroth; Tom Wingfield; Celso Khosa; Salla Atkins (Global Public Health)
Tuberculosis is recognised as a disease of the economically disadvantaged people due to its association with financial vulnerability. Mozambique still faces the challenge of the high burden of TB and associated costs. We aimed to understand the social and economic impacts of TB and the need for social support among people with TB in Mozambique. We conducted a qualitative study using a phenomenological approach focusing on the lived experiences and perceptions of people with TB. A total of 52 semi-structured one-to-one in-depth interviews were conducted and data were analysed using a reflexive thematic analysis. Three themes were drawn from the analysis: (i) TB has a social and economic impact that requires adaptation and resourcefulness amongst those affected; (ii) People with TB have different preferences and needs for social support, and (iii) People with TB have different knowledge of, and experiences with, formal social support. TB affects family and community relationships mainly due to impacts on the household’s finances. People with TB in Mozambique are not entitled to any form of social support, and they need to rely on help from family and the community which is often insufficient. Further investigation is needed on how social support schemes can be developed in Mozambique.